Applicability of Recombinant Laccases From the White-Rot Fungus Obba rivulosa for Mediator-Promoted Oxidation of Biorefinery Lignin at Low pH - Kontro, Jussi; Maltari, Riku; Mikkilä, Joona; Kähkönen, Mika; Mäkelä, Miia R.; Hildén, Kristiina; Nousiainen, Paula; Sipilä, Jussi (Frontiers in Bioengineering and Biotechnology, 2020)
Utilization of lignin-rich side streams has been a focus for intensive studies recently. Combining biocatalytic methods with chemical treatments is promising approach for sustainable modification of lignocellulosic waste streams. Laccases are catalysts in lignin biodegradation with proven applicability in industrial scale. Laccases directly oxidize lignins phenolic components, and their functional range can be expanded using low molecular weight compounds as mediators to include non-phenolic lignin structures. In this work, we studied recombinant laccases from the selectively lignin degrading white-rot fungus Obba rivulosa in detail for their properties and evaluated their potential as industrial biocatalysts for modification of wood lignin and lignin-like compounds. We screened and optimized various laccase mediator systems (LMS) using lignin model compounds and applied the optimized reaction conditions to biorefinery sourced technical lignin. In the presence of both N-OH-type and phenolic mediators, the O. rivulosa laccases were shown to selectively oxidize lignin in acidic reaction conditions, where co-solvent is needed to enhance lignin solubility. In comparison to catalytic iron(III)-TEMPO oxidation systems, the syringyl-type lignin units were preferred in mediated biocatalytic oxidation systems.